Sexual Abuse Breaking the Silence - Abac&#305, Ersi; Faikoğlu, Rehat (IntechOpen, 2012)
Sexual assault can be considered as expression of aggression through sex. This, in turn, can have serious negative effects on a survivor's social and occupational functioning. This book has been organized towards that specific approach, by compiling the scientific work of very well-known scientists from all over the world. The psychological victimization of sexual assault, the physiological aspect of sexual abuse and the different attitudes in coping with sexual assault based on different cultural backgrounds are analyzed. Having in mind that one solution may not necessarily be suitable for all cases, we hope that this book will open a debate on sexual assault for future practice and policy and that it will be a step forward to 'break the silence'.